Pornografi Sebagai Penyimpangan Pada Mahasiswa di Era Digital - Hisyam, Ciek Julyati; Seruni, Mayang Puti; Nuraini, Alya Alifah; Islamiya, Fahria Izzatul; Koputri, Keisa; Fauziah, Sipah; Kartika, Sri Yulia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The rapid development of digital technology facilitates access to various content, including pornography. This phenomenon is becoming increasingly worrying among students, given their high curiosity and weak supervision. Free access to pornography can lead to deviant behavior, psychological disorders, addiction, and dehumanization. This study aims to examine the behavior of consuming pornography among students as a form of social deviation, by reviewing its impact from individual and social aspects, and looking at the causal factors through the perspective of social control theory. The study was conducted using a qualitative descriptive method through in-depth interviews with informants at one of the state universities in Jakarta. The results of the study showed that pornography consumption is influenced by various factors such as the environment, peers, technology, and weak self-control, which ultimately have an impact on mental health, social relations, and perceptions of the body and sexuality.